Time trends in the incidence of essential tremor: Evidences from UK and France primary care data - Antonazzo, Ippazio Cosimo; Conti, Sara; Rozza, Davide; Fornari, Carla; Eteve-Pitsaer, Caroline; Paris, Claire; Gantzer, Laurène; Valentine, Dennis; Mantovani, Lorenzo Giovanni; Mazzaglia, Giampiero (Frontiers in Neurology, 2022)
Introduction: Although Essential Tremor (ET) is considered a common adult movement disorder, evidence on its incidence is still scant. This study aims at estimating ET incidence in two European countries: UK and France. Methods: Incident cases of ET were identified within the Health Improvement Network (THIN®) database between January 1st, 2014 and December 31st, 2019. Yearly crude and standardized incidence rates (IR) were estimated across the study period for both countries. Poisson regression models were built to assess temporal trends in IRs and differences between sexes and age classes. Results: 4,970 and 4,905 incident cases of ET were identified in UK and France, respectively. Yearly average crude IR (per 100,000 person-years) were 18.20 (95%CI: 15.09-21.32) in UK and 21.42 (17.83-25.00) in France, whereas standardized ones were 19.51 (18.97-20.01) and 19.50 (18.97-20.05). Regression analyses showed slightly increasing trends in both countries, higher incidence among males and a significant increase with age. Yearly average IR increased from 3.96 (0.95 - 6.97) and 5.28 (1.12 - 9.44) in subjects aged <20 years to 49.27 (26.29 - 72.24) and 51.52 (30.19 - 72.86) in those aged >80 year in UK and France. Conclusions: Standardized ET incidence was comparable in UK and France, showing a slight increase in both countries, reporting higher value among people aged 60 years and older. This study outlines the need to conduct future studies to estimate the burden of ET in terms of disease control and healthcare resources utilization.